Local Networks of Resilience and Climate Adaptation: The Case of Istanbul - (:unkn) unknown (Springer, 2016)
Large coastal cities are often the engines of national growth but also tend to be areas with high sensitivity to the impacts of climate change. Therefore, integrated adaptation plans are essential for turning them into resilient cities. National competitiveness strategies are, however, increasingly at odds with the very idea of resilient cities, either forcing urban sprawl to its limits or transforming green spaces into grey spaces within the city. In the midst of heated conflict about how to use public land, the role of networks of local initiatives to protect green spaces and residential rights of poor and marginal groups becomes pivotal to achieve equity and urban resilience. The aim of this paper is to explore the dynamics of such networks in Istanbul and investigate how to integrate them into local climate change adaptation plans. Conflicts over Istanbul’s historical urban vegetable gardens (bostan) and the construction of the third bridge are good examples of sites of contestation which, unless resolved, seriously hinder any possibility of agreement and action on climate adaptation plans. © 2016, Springer International Publishing Switzerland.
Keywords: Climate change; Green spaces; Local adaptation; Resilience; Urban farming